Development of Furo[2,3-b]quinoline Derivatives with Anti-Breast Cancer Property by Targeting Topoisomerase II - Wang, Ying; Li, Na; Jiang, Neng; Chen, Li; Sun, Jianbo (Anti-Cancer Agents in Medicinal Chemistry, 2021)
A number of novel furo[2,3-b]quinoline derivatives were designed and synthesized by introducing different substituted anilines and phenols to C4-position of furo[2,3-b]quinoline. All target compounds were evaluated in vitro against two human breast cancer cell lines (MCF-7 and MDA-MB-231) and one normal breast cell (MCF-10A) by MTT (3-[4,5-dimethylthylthiazol-2-yl]-2,5 diphenyltetrazolium broide, Thiazolyl blue) method. Most derivatives showed significant cytotoxic activity on the two breast cancer cells with IC50 values in the range of (5.60-26.24 μM) and a certain selectivity, especially in the inhibition of MDA-MB-231. More notably, they were less toxic to normal breast cell (MCF-7-10A). Compound I7 could be considered as an ideal selective candidate for further study. Mechanism studies showed that I7 could inhibit the proliferation of cells by arresting MDA-MB-231 cell cycle at G2/M phase. Overall, as a novel furo[2,3-b]quinoline derivative, I7 exhibited an excellent inhibitory effect in MDA-MB-231 cell and was worthy of in-depth study.
Keywords: MTT